RATIO DECIDENDI PUTUSAN HAKIM YANG BERBEDA DARI KASUS SEJENIS DALAM DELIK NARKOTIKA - Satrya Manulung Bansage Immanuel Paparang; Dian Adriawan Daeng Tawang (Fakultas Hukum Universitas Trisakti, 2022)
The legal proposition, which is a predicate that comprises the consideration of the judge making a legal decision on the case being tried, say the case of drug use, contains the ratio decidendi of the court's decision. The way the issue is phrased is how are different judge decisions on the ratio determined (Decision of the South Jakarta District Court No.968/Pid.Sus/2020/PN.Jkt.Sel and Decision of the Malang District Court No.28/Pid.Sus/2020/PN.Mlg); and how are abuse addicts and drug abuse victims handled? The study methodology employed is normative juridical, which examines judicial rulings, statutes and regulations. The study's findings, analysis, and conclusions. There are discrepancies in the way judges imposed legislation when compared to the two verdicts in the drug case. If you look at the ratio decidendi of the punishment, it is obvious that the judges who tried the case were inconsistent in their assessments of the defendant's degree of behavior in light of the various grounds they used to reach their judgment.